The cost of treating diabetic ketoacidosis in an adolescent population in the UK: a national survey of hospital resource use. Issue 8 (23rd January 2019) - Dhatariya, K. K.; Parsekar, K.; Skedgel, C.; Datta, V.; Hill, P.; Fordham, R.
Abstract: Aims: Adolescents with Type 1 diabetes commonly experience episodes of ketoacidosis. In 2014, we conducted a nationwide survey on the management of diabetic ketoacidosis in young people. The survey reported how individual adolescents with diabetes were managed. However, the costs of treating diabetic ketoacidosis were not reported. Methods: Using this mixed population sample of adolescents, we took a 'bottom‐up' approach to cost analysis aiming to determine the total expense associated with treating diabetic ketoacidosis. The data were derived using the information from the national UK survey of 71 individuals, collected via questionnaires sent to specialist paediatric diabetes services in England and Wales. Results: Several assumptions had to be made when analysing the data because the initial survey collection tool was not designed with a health economic model in mind. The mean time to resolution of diabetic ketoacidosis was 15.0 h [95% confidence interval (CI) 13.2, 16.8] and the mean total length of stay was 2.4 days (95% CI 1.9, 3.0). Based on data for individuals and using the British Society of Paediatric Endocrinology and Diabetes (BSPED) guidelines, the cost analysis shows that for this cohort, the average cost for an episode of diabetic ketoacidosis was £1387 (95% CI 1120, 1653). Regression analysis showed a significant cost saving of £762 (95% CI 140, 1574; P = 0.04) among those treated using BSPED guidelines. Conclusion: We have used a bottom‐up approach to calculate the costs of an episode of diabetic ketoacidosis in adolescents. These data suggest that following treatment guidelines can significantly lower the costs for managing episodes of diabetic ketoacidosis. What's new?: Adolescents with Type 1 diabetes frequently experience diabetic ketoacidosis. However, how much treating this condition costs in this age group remains unknown in the UK. We used the 2014 national survey data set to conduct a novel, 'bottom‐up' approach to cost analysis. Our data suggest that the average cost of an episode of diabetic ketoacidosis in an adolescent in the UK in 2014 was £1387. Use of the British Society of Paediatric Endocrinology and Diabetes guidelines was associated with a significant £762 reduction in costs.